Correlation of the structural and morphological property of the formation of ZnO nanoparticles using Ricinus Communis extract as a ligand and synthesized through two different precipitating agents. (August 2021) - Gutiérrez, Nancy; Tiwari, Dhirendra Kumar; Villegas, Javier; Reynoso, Francisco
Abstract: The present work defines the structural and morphological behavior of ZnO nanoparticles (ZnONP) synthesized via using Ricinus Communis (Castor) extracts. Two precipitating agents (bases) were used to regulate the pH (10), in presence of this natural extract the determination of structural, morphological and functional groups availability was performed to evaluate the enhancement in crystallite size, shape formation and colloidal stability of the nanoparticle.